Effectiveness of Online Mediation Response to Divorce Law in Religious Courts in The Era of Pandemic Covid-19 - Reskia, Reskia (IAIN Parepare, 2022)
This thesis discusses the use of communication technology to be able to become a solution and a means to support the effectiveness and efficiency of the peace process in online mediation in the Religious Courts. The objectives of the thesis research include: (1) to find out the trend of divorce cases being sued in the Religious Courts, the urgency of implementing and the effectiveness of implementing online mediation in the era of the Covid-19 pandemic. (2) to determine benchmarks for the effectiveness of mediation in the Religious Courts and (3) to determine the effectiveness of online mediation for contested divorces in the Religious Courts during the Covid-19 pandemic era. This type of research is field research and development (Research and Development) with a sociological juridical approach. The primary data source is in the form of interview data from three informants, namely, the Deputy Chairperson of the Court and the Mediator and is supported by observation and documentation in the form of files or documents related to divorce cases being contested at the Class 1 B Parepare Religious Court. The data in this study were analyzed qualitatively descriptively by testing the validity of the data using the triangulation technique. The results of this study indicate that (1) during the Covid-19 pandemic, the tendency for divorce cases to be sued at the Parepare Religious Court did not experience a significant change in the number of cases, only in April and May there was a decrease in the number of divorce cases due to the government's policy of restrictions related to emergencies health and the policy of the Parepare Religious Court which limits the number of cases that justice seekers wish to register. (2) Five factors that influence law enforcement, these five factors become benchmarks for measuring the effectiveness of mediation in the Religious Courtsnamely, legal factors, law enforcement factors, infrastructure factors, community factors and cultural factors. So that in divorce cases the benchmark for the success of mediation is the number of cases revoked (3)Mediation conducted online has not been effective as an alternative to dispute resolution in an effort to reconcile the parties who wish to file for divorce, so it is necessary to update the law regarding the regulations governing online mediation which are equipped with telecommunication infrastructure, security systems, and online mediation institutions, especially during the Covid pandemic -19.